Prevalence of consumption of smokeless tobacco products and exposure to second-hand smoke among women in the reproductive age group in a rural area of Koppal, Karnataka - B Y Yuvaraj; Vijaykumar P Mane; Mallappa Biradar; Virupakshappa Nayaka; Rashmi Sreenivasamurthy (Wolters Kluwer Medknow Publications, 2020)
Background: Tobacco use is one of the most important causes of death and disease globally. Nearly one-third of the population in India uses tobacco, and smokeless form is culturally acceptable even among women. Objectives: (1) To estimate the prevalence of consumption of smokeless tobacco (SLT) products among women in the reproductive age group in the study setting. (2) To determine the various factors associated with the consumption of SLT. (3) To estimate the prevalence of exposure to second-hand smoke among the study participants. Materials and Methods: A cross-sectional study was conducted in the field area of primary health center Irkalgad, Koppal in March 2018. A cluster sampling technique was used and a total of 829 women were included. Data were collected using pretested and semi-structured questionnaire and analyzed using the Epi info software version 3.5.4 (Centers for Disease Control and Prevention" (CDC), Atlanta, Georgia, United States of America). Results: The prevalence of consumption of SLT products was 17.85%, and the most common product consumed was tobacco with betel quid. Tobacco consumption was found to be significantly associated with age, literacy, marital, and employment status of the study participants. Conclusion: The present study concludes that SLT consumption is high among women in the reproductive age group in the study setting and identifies multiple determinants for effective planning of interventions.